Dominica. Significant achievements 2010-2017 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2017)
The main activities carried out by the Institute in Dominica are identified, during the period from 2010 to 2017, with respect to the needs and interests of the country, strengthening issues such as good agricultural practices, post-harvest management, new technologies, export, resilience against climate change, improve quality standards in manufacturing and packaging. Likewise, technical support was provided to women for their inclusion in agriculture and in the improvement of the value chains of vegetables, onions and ruminants. Finally, work was done on food security and exports.